The Feasibility study and indicators of technological excellence in the monotheistic context - Yousef farshadnia; Ahmad Shahgoli (مطالعات بنیادین تمدن نوین اسلامی, 2022)
Technology is a phenomenon that has been accounted for by Muslim scholars from various perspectives. The instrumental, independent and interactive views are among the views put forward in the statement of the relationships between religion and technology. The subject of the present study is the feasibility of technological excellence in the context of monotheistic thought and the essence of its characteristics. The method of data collection is the documentary study and the data has been analyzed using the descriptive method in this research. The findings indicate that, firstly, the discussion and realization of technology in a monotheistic context based on principles such as (a) the religion , its relation and monotheistic governance over all aspects of human life, (b) the comprehensiveness of religion, (c) the relationship between worldly and the hereafter life, as well as (d) the technological orientation is feasible. Secondly, the following basic indicators have a strategic role in the excellence of technology in the monotheistic context, the movement towards the engineering and the realization of the modern Islamic civilization, and finally, the worldly and the hereafter bliss of the human being: (1) the alignment with the teachings and principles of religion (a. monotheism and b. resurrection orientation), (2) the alignment with the purpose and destination of human creation and his/her bliss, (3) the alignment with the instinctive and actual needs of human beings (a. the real and non-false needs of human beings, b. the principle of contentment and avoidance of extravagance and consumerism, c. the human dignity, d. the finality, and e. the honorability and anti-despotism), and (4) the alignment with the creation system and the environment (a. the stability and beauty and b. the harmony with the environment).